Review and three new species of the flat bug genus Neochelonoderus Hoberlandt, 1967 from East Africa (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Grebennikov, Vasily (Zootaxa, 2015)
The apterous East African Mezirinae flat bug genus Neochelonoderus Hoberlandt 1967 is revised. In addition to known species from Burundi (N. basilewskyi) and Democratic Republic of the Congo (N. straeleni), two new species from Tanzania (N. talaus n. sp. and N. areius n. sp.) and one from Zambia (N. hoberlandti n. sp.) are described and illustrated. A key to the species of Neochelonoderus is presented.